Examining Behavioral Biases among Investors in the Saudi Arabian Stock Market: - Al Rahahleh, Naseem (STIE Malangkucecwara, 2025)
This paper presents an explanatory study of the prevalence and influence of behavioral heuristics and prospect biases among investors in the Saudi stock market with the specific goal of determining the extent to which these biases impact investment decisions. Data were collected through an online questionnaire completed by 598 investors, and a statistical analysis was performed to determine the prevalence and impact of identified biases. The data were analyzed using descriptive statistics, and the mean values were tested using a one-sample t-test. In addition, one-way analysis of variance (ANOVA) was conducted to determine significant differences based on demographic and trading variables. The results indicate that investors in Saudi Arabia show moderate behavioral biases, with variations in how these influence investment decisions. Representativeness and regret aversion emerged as the most prominent bias, with a high level of each observed. Age, income, education, trading experience, and trading frequency were significant factors influencing. the degree of bias The findings of this study, therefore, have important implications for investors and policymakers in the KSA context, highlighting a need for initiatives that promote rational decision-making and reduce the impact of behavioral biases on investors.